2020
DOI: 10.13078/jsm.200004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Non-Dipper and Reverse-Dipper Pattern with Sleep Quality in Normotensive Patients

Abstract: It has been observed in many different populations that circadian blood pressure (BP) patterns have a significant impact on cardiovascular (CV) results. Important predictors of CV morbidity and mortality are known as non-dipper (ND) and reverse-dipper (RD) BP pattern. RD and ND patterns are frequently encountered in many normotensive patients in daily practice. Methods: The purpose of this study is to evaluate the frequency and quality of sleep, especially in normotensive young individuals, by using sleep ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This could be due to a higher mean body mass index of the cohort (around 29 kg/m 2 ) and the presence of different comorbidities (diabetes, thyroid dysfunction and dyslipidemia) in 29% of individuals, which are known to reduce the nocturnal decline in BP [ 23 , 37 ]. In this study, they also observed significant differences in sleep time and sleep quality among “dippers”, “non-dippers” and “risers” [ 18 ]. Reduce sleep time was associated with decreased nocturnal systolic BP variability and riser profile [ 18 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This could be due to a higher mean body mass index of the cohort (around 29 kg/m 2 ) and the presence of different comorbidities (diabetes, thyroid dysfunction and dyslipidemia) in 29% of individuals, which are known to reduce the nocturnal decline in BP [ 23 , 37 ]. In this study, they also observed significant differences in sleep time and sleep quality among “dippers”, “non-dippers” and “risers” [ 18 ]. Reduce sleep time was associated with decreased nocturnal systolic BP variability and riser profile [ 18 ].…”
Section: Discussionmentioning
confidence: 77%
“…In this study, they also observed significant differences in sleep time and sleep quality among “dippers”, “non-dippers” and “risers” [ 18 ]. Reduce sleep time was associated with decreased nocturnal systolic BP variability and riser profile [ 18 ]. Several studies have previously described the impact of sleep troubles on circadian BP [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 77%
“…38,39 The reverse dipping pattern is adversely associated with sleep quality and time. 42 Some studies discovered that a reverse dipping pattern was more likely to be associated with obstructive sleep apnea, 43,44 and sleep fragmentation, and intermittent hypoxia might trigger sympathetic activity and result in elevated BP at night. 45 In a retrospective cohort study, obstructive sleep apnea was a significant predictor of AF incidence (HR 2.18, 95% CI: 1.34-3.54).…”
Section: Possible Mechanisms From Reverse Dipping To Afmentioning
confidence: 99%